The possible effects of mono butyl phthalate (MBP) and mono (2-ethylhexyl) phthalate (MEHP) on INS-1 pancreatic beta cells - Karabulut, Gözde (Toxicol Res (Camb), 2021)
Mono-2-ethyhexyl phthalate (MEHP), an environmental xenoestrogen, is widely used in the production of polyvinyl chloride materials and can be easily accumulated in human body. MBP is the active monoester metabolite of di butyl phthalate that is widely used as plasticizer in many products such as plastic toys, food packaging, personal care products, as well as an additive in lubricants, eliminating foams, and lotions. The presented in-vitro cytotoxicity study focused on time-dependent and combinatory exposure scenarios. We chose these phthalates because they are posed a considerable interest because of their contribution to insulin resistance, type-2 diabetes and obesity. All experiments performed in INS-1 pancreatic beta cells show moderate cytotoxicity with a time-dependent increase in effectiveness. INS-1 cells were treated with 0.001, 0.01, 0.1, 1, or 10-μM MEHP and MBP for 24, 48, and 72 h. Our results showed that cell viability was decreased and total oxidant levels were increased. Also, mRNA expression levels with asscociated beta cells were measured and for MBP dose groups, all mRNA expression levels were decreased. In conclusion, these findings suggest that, MEHP and MBP are have a negative and distruptor role on pancreatic beta cells and it will be linked with insulin resistance and type 2 diabetes.